2021
DOI: 10.3389/fpls.2021.645150
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cadmium Storage Forms and Isotope Ratios in Rice During Grain Filling

Abstract: Rice poses a major source of the toxic contaminant cadmium (Cd) for humans. Here, we elucidated the role of Cd storage forms (i.e., the chemical Cd speciation) on the dynamics of Cd within rice. In a pot trial, we grew rice on a Cd-contaminated soil in upland conditions and sampled roots and shoots parts at flowering and maturity. Cd concentrations, isotope ratios, Cd speciation (X-ray absorption spectroscopy), and micronutrient concentrations were analyzed. During grain filling, Cd and preferentially light Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 132 publications
(214 reference statements)
2
45
1
Order By: Relevance
“…In most cases, shoots were isotopically heavier than roots in wheat, barley, rice, cacao, and a Cd accumulator plant ( Wiggenhauser et al, 2016 , 2021a , b ; Wei et al, 2018 ; Imseng et al, 2019 ; Moore et al, 2020 ; Wang et al, 2021 ; Zhong et al, 2021 ; Figure 10 ). The retention of light Cd isotopes in roots of cereals and numerous different cacao genotypes was ascribed to vacuolar sequestration.…”
Section: Isotope Fractionation In Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…In most cases, shoots were isotopically heavier than roots in wheat, barley, rice, cacao, and a Cd accumulator plant ( Wiggenhauser et al, 2016 , 2021a , b ; Wei et al, 2018 ; Imseng et al, 2019 ; Moore et al, 2020 ; Wang et al, 2021 ; Zhong et al, 2021 ; Figure 10 ). The retention of light Cd isotopes in roots of cereals and numerous different cacao genotypes was ascribed to vacuolar sequestration.…”
Section: Isotope Fractionation In Plantsmentioning
confidence: 99%
“…Cd isotope composition in reproductive and shoot organs can strongly differ (Δ 114/110 Cd reproductive-shoot.organ −0.30 to +0.50‰, Figure 10 ). While Rayleigh fractionation modeling for different plants suggests dominantly unidirectional xylem flow from roots to shoots ( Wiggenhauser et al, 2016 ; Wei et al, 2018 ; Moore et al, 2020 ), it has been shown that cereals likely use phloem redistribution on grain filling ( Wiggenhauser et al, 2021b ; Zhong et al, 2021 ). In rice, an important hub for the transfer of Cd from the xylem to the phloem are the nodes ( Yamaji and Ma, 2014 ).…”
Section: Isotope Fractionation In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Recently, node I of rice plants was found to be strongly enriched in heavier isotopes relative to the shoot and flag leaf under drained conditions, even though Cd in node I was exclusively bound to S ligands. 31 It is supposed that membrane transport, rather than Cd speciation, governed the isotope fractionation during xylem-to-phloem transfer in the nodes. 31 Nodes of rice plants serve as a hub for the distribution of minerals, including Cd, to the grains.…”
Section: Introductionmentioning
confidence: 99%